0679 Impaired Visual Processing In Rbd Patients: A Visual Search Task Study. (27th April 2018) - Giora, E; Galbiati, A; Zucconi, M; Ferini-Strambi, L
Abstract: Introduction: Rapid Eye Movement (REM) sleep Behavior Disorder (RBD) is a REM sleep parasomnia known to be strongly associated with the development of neurodegenerative disorders. Cognitive deterioration has been shown to be a common issue in RBD patients, in particular impairments in visuo-spatial abilities. However, little is known about the effect of RBD on visual processing. The aim of this study was to evaluate the basic mechanisms of stimulus analysis in RBD patients by a visual search paradigm. Methods: 12 RBD patients (mean age: 68.25 ± 9.63, 9 males) and 12 age-matched healthy controls (HC) were enrolled in the study. After a nocturnal video-polysomnographic recording, patients performed a visual search task in which they had to detect the presence/absence of a target (letter T) embedded in the 50% of trials into a set of distractors (letters Os, Xs, or Ls). Target's salience and distractors' numerosity were manipulated as independent variables, whereas accuracy and reaction times (RT) were recorded as dependent variables. Results: Typical effects of visual search were confirmed: RT increased with distractors' number and decreased with targets' salience. RBD patients showed significantly slower RT in comparison with HC. Furthermore, analyzing RT of stimuli containing the target in comparison to RT of stimuli in which the target was absent, patients differed from controls only in the condition of target absent. This result indicates a perceptual impairment specifically related to the exhaustive visual analysis, according to the Sternberg's model. Conclusion: These results experimentally demonstrates a perceptual impairment revealed by the more demanding conditions of the visual search task. This impairment seems to be in line with previous neuropsychological researches that showed the presence of a visuo-spatial deficit in RBD patients. Support (If Any): none.